TEACHERS’ PERCEPTIONS TOWARD COOPERATIVE LEARNING IMPLEMENTATION IN EFL CLASSROOMS - Eka Kartika Fitrianti (Universitas Negeri Manado, 2021)
In teaching-learning English, the teaching-learning method is essential that should be available in the school. The teaching-learning method in this study is Cooperative Learning. CL is a student-center learning method. CL allows students to have a group discussion about conducting the task. The teachers' CL as the teaching advice in planning the students’ activities in the classroom. Meanwhile, the students used Cooperative Learning as the learning method in obtaining the subject lesson. Regarding the Cooperative Learning issue, the researcher conducted the study of the Cooperative Learning implementation based on the teachers’ perspectives. This research investigates the teachers’ perceptions of the Cooperative Learning implementation and explores the students’ changes found by teachers in EFL classrooms. This research implemented a qualitative case study in gaining the data, by using questionnaire and interview. The data were analyzed descriptively. The research participants were three English teachers who taught using Cooperative Learning method. The results showed that the teachers perceived Cooperative Learning positively. Cooperative Learning was suitable to the students’ needs in achieving learning goals. In choosing the appropriate Cooperative Learning, the school environment and students’ background needed to be considered. Cooperative Learning fostered students’ independence in fulfilling the assignment. While Cooperative Learning attractions, students looked enjoying the learning process. They seemed more active in conducting class activity. In addition, according to students’ personal benefits, Cooperative Learning method influenced students’ self-esteem, self-confidence, motivation, and interest in learning English.